Aluminum sulfate and copper sulfate as additives in kamias (Averrhoa bilimbi Linn) preserve - Lorenzana, Maria Agnes S.; Guzman, Matilde P. (1980.)
This study was conducted with the main purpose of determining a most acceptable method of preserving kamias in syrup based on a simple method and effect of various levels of aluminum sulfate ans copper sulfate on the firming and color fixation respectively. The basic procedure developed by Guzman (1980) was followed. The kamias preserved procedure from the simple basic method was characterized as brownish, firm, moderately shriveled and too sweet. Results of the tests utilizing additives showed that the use of aluminum sulfate was not necessary, since firmness was developed during the plumping stages. An improvement in color was noted with the use of copper sulfate. Stepping-up pf the sugar concentration was performed and the resulting product was only slightly shriveled. The modified method used was translated into a simple kitchen procedure which could be duplicated by others to yield a good quality kamias preserve.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food additives; Aluminum sulfate; Copper sulfate